Band of brothers (and sisters): gender framing in U.S. Army commercial advertising and the role of gender in on-the-ground recruitment strategies - Pate, Holly (Kansas State University, 2020)
The U.S. Army spends more than 7 billion dollars in recruitment advertising, with its largest percentages going toward television marketing. However, little research has been dedicated to military advertising and recruiting efforts besides strategic recommendations. This thesis offers a critical investigation on the depiction of gender in military advertising and on-the-ground recruiting. This study uses a mixed-methods approach involving the collection of both quantitative and qualitative data in a single study on Army recruitment in relation to gender. First, a content analysis on a sample of U.S. Army commercials produced between 2008 and 2018 offers an exploratory discussion on the Army’s advertorial recruitment. Second, longform interviews with present and past recruiters shares a view of on-the-ground recruiting strategies of the U.S. Army over the last decade, and how gender plays a role.
Keywords: Advertising; Framing Theory; Military; Army Commercials; Army Recruitment